(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
In high-mountain areas, glacial lake outbursts often cause floods and extreme events. The study of such phenomena is especially important in the context of ongoing intensive glacier melting and climate change. This study is devoted to the monitoring of the Bashkarinsky glacial lakes after their outburst on September 1, 2017. The lakes are located in the most densely populated part of the Central Caucasus, in the Elbrus Region. After the outburst, the lake system became flowing, but since then it has undergone significant changes, remaining unstable and potentially dangerous. The study used remote sensing data and field observations to assess the state of the Bashkarinsky Lakes. Potential scenarios for a repeated outburst of Lake Bashkara were also simulated based on the STREAM_2D hydrodynamic model.